Example of Shostakovich for the Conversion of Music to Photography - Uysal, Hüseyin (Bahattin AYDINLI, 2021)
Art is a form of expression. This expression process can be realized with different materials. In this research, two branches of art with different materials are emphasized; music and photography. One is from the phonetic arts group and the other is from the plastic arts group. In this research, it is aimed to examine the conversion of music to photography. For this purpose, the famous Russian composer Shostakovich's String Quartet No: 8 was played by 5 different young artists who received photography training. Young artists were asked to take a photo shoot for each part of the work, which consists of 5 movements: largo, allegro molto, allegretto, largo and largo, in which the political events of the period are handled. It has emerged as a result that young artists, who shoot independently of each other, produce conflict and depressed works with the theme of war in accordance with the subject of music. Dark stain dominates in their composition. The dominant use of the color black, one of the effects of mourning on psychology, while using this dark stain is an important result.
Keywords: Sanat; Disiplinler Arası Sanat; Fotoğraf; Müzik; Shostakovıch